The Obama portraits - Caragol-Barreto, Taina Beatriz; Moss, Dorothy; Powell, Richard J., 1953-; Sajet, Kim (National Portrait Gallery, Smithsonian Institution ; Princeton University Press, 2020)
"This is the first study of the portraits Barack Obama (2018) and Michelle Obama (2018), their reception, and their significance. The book includes essays by historians examining the influence of the paintings and what they reveal about contemporary portraiture, particularly in relation to American and African American history and culture. The book also features interviews with the artists, transcripts of the remarks made by the Obamas at the unveiling, and a selection of images, including behind-the-scenes photography by Pete Souza, the official photographer for the Obamas, made during the portrait sittings"--